2001
DOI: 10.2166/wst.2001.0805
|View full text |Cite
|
Sign up to set email alerts
|

State of the art for animal wastewater treatment in constructed wetlands

Abstract: Although confined animal production generates enormous per-unit-area quantities of waste, wastewater from dairy and swine operations has been successfully treated in constructed wetlands. However, solids removal prior to wetland treatment is essential for long-term functionality. Plants are an integral part of wetlands; cattails and bulrushes are commonly used in constructed wetlands for nutrient uptake, surface area, and oxygen transport to sediment. Improved oxidation and nitrification may also be obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 0 publications
0
51
1
1
Order By: Relevance
“…The application of aquatic plants for treatment of animal wastes has mainly involved constructed wetlands. Currently, livestock producers in at least 26 states across the USA use constructed wetlands to treat animal production wastewater (Hunt and Poach, 2001). Constructed wetlands have an appeal as a farm waste management practice because they are a low cost, simple technology, and ideally require little maintenance or management after construction (Hammer, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The application of aquatic plants for treatment of animal wastes has mainly involved constructed wetlands. Currently, livestock producers in at least 26 states across the USA use constructed wetlands to treat animal production wastewater (Hunt and Poach, 2001). Constructed wetlands have an appeal as a farm waste management practice because they are a low cost, simple technology, and ideally require little maintenance or management after construction (Hammer, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhao et al, (2004a) reported on the use of a novel laboratory-scale reed bed system for the treatment of an animal farm wastewater with a BOD 5 value of 441-3150mg/l while Hunt et al, (2001) detailed the successful application of CWs to the treatment of wastewater from dairy and swine operations.…”
Section: Discussionmentioning
confidence: 99%
“…These include nuisance odours, pathogens, concentrated wastewater, inadequate land treatment sites, residential encroachment and new regulations (Hunt and Poach, 2001). In particular, the steady intensification of such farming practices have led to increasing levels of environmental pollution, including degradation of the water quality of downstream ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Hunt and Poach (2001) reported that the common practice on most animal farms is to apply both solid and liquid waste to land for terminal treatment. In Ireland, it is reported that dairy parlour washings are treated mainly by land spreading with low irrigation systems (Healy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation